2015
DOI: 10.1002/joc.4309
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal characteristics of the recent rainfall recovery in West Africa

Abstract: Using daily (monthly) rainfall data from 167 (254) stations across West Africa with at least 80% data availability for the 31-year period 1980-2010 and the gridded African Rainfall Climatology Version 2 (ARC2) for the period 1983-2010, linear trends in yearly and monthly rainfall totals were investigated. Measures of the Expert Team on Climate Change Detection and Indices (ETCCDI) and two rainy season onset and retreat definitions were employed to assess the corresponding trends in frequency and intensity of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
163
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(208 citation statements)
references
References 43 publications
(73 reference statements)
40
163
0
5
Order By: Relevance
“…Taylor et al [5] identified, using satellite infrared temperature (IRT) data, a robust and strong positive trend in the frequency of intense Sahelian mesoscale convective systems (MCS) since 1982 (in which MCS-mean IRT was used as a measure of intensity). Similar conclusions emerge from Sanogo et al [106] and Zhang et al [107].…”
Section: Main Trends Described In Recent Worksupporting
confidence: 81%
“…Taylor et al [5] identified, using satellite infrared temperature (IRT) data, a robust and strong positive trend in the frequency of intense Sahelian mesoscale convective systems (MCS) since 1982 (in which MCS-mean IRT was used as a measure of intensity). Similar conclusions emerge from Sanogo et al [106] and Zhang et al [107].…”
Section: Main Trends Described In Recent Worksupporting
confidence: 81%
“…Moreover, an increase in heavy-rainfall events and prolonged dry spells have been observed and are projected for the future (Sanogo et al, 2015;Taylor et al, 2017;Zhang et al, 2017). Our results showed that the semi-arid zone will be most prone to these projected changes, and an increase in heavy-rainfall events, a delay in the onset of the wet season and dry spells exceeding 14 days will cause a significant reduction in vegetation productivity, although the annual rainfall amount may be constant or even increasing.…”
Section: Discussionmentioning
confidence: 67%
“…Several studies have reported a tendency towards an earlier start of the wet season (Sanogo et al, 2015;Zhang et al, 2017), but projections predict a delay of the wet season in the later 21th century (Biasutti and Sobel, 2009;Guan et al, 2014). Moreover, an increase in heavy-rainfall events and prolonged dry spells have been observed and are projected for the future (Sanogo et al, 2015;Taylor et al, 2017;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contrast between a dryer western Sahel and a wetter eastern Sahel is becoming more significant (Lebel and Ali, 2009;Nicholson, 2013). Sanogo et al (2015) found a statistically significant positive rainfall trend between 1980 and 2010; however, it did not reach the degree of wetness of the 1950s.…”
Section: Introductionmentioning
confidence: 90%